2010
DOI: 10.1055/s-0029-1225351
|View full text |Cite
|
Sign up to set email alerts
|

Leydig-Cell-Tumor of the Ovary that Responded to GnRH-Analogue Administration – Case Report and Review of the Literature

Abstract: Progressive hirsutism can be a symptom of an androgen-producing tumor, especially in postmenopausal women. We report a case of a 58-year-old woman who complained of progressive hirsutism, nervousness, irritability, anxiousness and an increased libido. Examination showed an unusual redness of her head, décolleté, palms and soles of her feet. Basal laboratory tests revealed a profound elevation of testosterone levels (7.5 microg/l) and normal levels of androstendione, dehydroepiandrosterone-sulfate, 17alpha-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…Mahmoodi M et al found 5 the mean total volume of ovary, cortex, medulla and the number of follicles significantly increased in the grafts +EPO group (p < 0.01) than control one. Trošt N et al analyzed 6 11 polyglobulia and a Leydig cell tumor in the hilus and stroma of the left ovary in a 58-year-old woman whose basal laboratory tests were normal for levels of 17alpha-hydroxy-progesterone and EPO. Kwon BK et al reviewed 12 the available neuroprotective therapies including EPO and progesterone administered for acute SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoodi M et al found 5 the mean total volume of ovary, cortex, medulla and the number of follicles significantly increased in the grafts +EPO group (p < 0.01) than control one. Trošt N et al analyzed 6 11 polyglobulia and a Leydig cell tumor in the hilus and stroma of the left ovary in a 58-year-old woman whose basal laboratory tests were normal for levels of 17alpha-hydroxy-progesterone and EPO. Kwon BK et al reviewed 12 the available neuroprotective therapies including EPO and progesterone administered for acute SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Im Falle von Metastasen kann eine platinbasierte Chemotherapie verabreicht werden, auch wenn valide, prospektive Daten zu ihrer Wirksamkeit fehlen [1]. Interessanterweise gibt es auch Fallberichte, die von einem Ansprechen der Erkrankung auf GnRH Analoga berichten [5,11].…”
Section: Prognoseunclassified
“…Eine neu aufgetretene, sich rasch entwickelnde ausgeprägte Virilisierung mit exzessiver Hyperandrogenämie ist bis zum Beweis des Gegenteils tumorverdächtig [3]. Tritt ein deutlicher Hirsutismus erstmals in der Postmenopause auf, so ist dies häufig ein klinisches Zeichen für einen androgenproduzierenden Tumor [4]. Des Weiteren wird die Bestimmung von Androstendion sowie von Dehydroepiandrosteronsulfat (DHEAS) empfohlen [9], das bei Frauen als Prohormon des Testosterons zu 90% in der NNR und zu 10% in den Ovarien produziert wird.…”
Section: Hyperandrogenismusunclassified
“…Bei postmenopausalen Patientinnen und nachgewiesener ovarieller Neoplasie wird eine beidseitige Adnexektomie durchgeführt. Bei Malignität wird stadiengerecht vorgegangen.E Eine organerhaltende Resektion wird bei Frauen im reproduktionsfähigen Alter angestrebt.Bei androgenproduzierenden Ovarialtumoren mit Tumorzellen, die Gonadotropinrezeptoren exprimieren, kann eine therapeutische Androgensuppression durch Einsatz von GnRH-Analoga wie Triptorelin erzielt werden[4]. Wird ein androgenbildender Tumor der NNR diagnostiziert, kann dieser ebenfalls laparoskopisch exstirpiert werden.…”
unclassified